Influence of Vertical Facial Growth Pattern on Herbst Appliance Effects in Prepubertal Patients: A Retrospective Controlled Study - Maria Rita Giuca; Marco Pasini; Sara Drago; Leonardo Del Corso; Arianna Vanni; Elisabetta Carli; Antonio Manni (International Journal of Dentistry)
Introduction. The Herbst device is widely used for correction of class II malocclusions; however, most of the researches carried out on the Herbst appliance in literature do not take into account patients with a different mandibular divergence. The aim of this study was to investigate the effects of Herbst on dental and skeletal structures and to evaluate possible influence of vertical facial growth patterns. Methods. A retrospective study was conducted on lateral cephalograms of 75 growing patients (mean age: 9.9 ± 1.9 years) with class II malocclusion treated with Herbst. Subjects were divided into 3 groups using the mandibular divergence index (SN and GoMe angle). Cephalometric parameters were evaluated using the modified SO (sagittal occlusion) Pancherz’s analysis. A statistical analysis was conducted to evaluate differences among groups using ANOVA. Results. Our study showed differences in response to treatment depending on patient’s facial vertical growth pattern. Cranial base angle and mandibular rotation were significantly different (p<0.05) between hypodivergent patients and normodivergent patients and between hypodivergent and hyperdivergent subjects. Conclusion. Hypodivergent patients increased their mandibular divergence during treatment to a greater extent than normodivergents; moreover, hyperdivergent patients exhibited a decreased mandibular divergence at the end of the treatment.